Pendampingan Peningkatan Kebersihan pada Penggemukan Kambing di Ponpes Darul Qur’an Sumbersari Kencong Kepung Kediri - M. Imam Maghfuroh; Miftahul Arif (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2021)
Researchers perform the task of mentoring the community in fattening ponpes darul qur'an dusun sumbersari village kencong subdistrict besieged Kediri regency to fulfill the meaning of tridarma college. Researchers conducted assistance on fattening goat ponpes darul qur'an because there is a problem complained by the goat manager, namely the presence of goats that are maintained experiencing disease attacks, and very irregular value of cleanliness, which may be in the absence of hygiene value makes the goats stricken with disease. Therefore, researchers made an initiative to create an agenda of hygiene improvement activities in fattening goats. Because the notion of cleanliness is a state free from dirt, including, dust, garbage, and odors. Therefore, researchers made an initiative to create an agenda of hygiene improvement activities in fattening goats. Because the notion of cleanliness is a state free from dirt, including, dust, garbage, and odors. In modern times, after Louis Pasteur discovered the process of transmitting diseases or infections caused by microbes, cleanliness also means being free from viruses, pathogenic bacteria, and harmful chemicals, which of course the existence of hygiene activities will prevent the spread of disease. The approach of researchers to the goat manager uses PAR techniques and research that researchers undergo using qualitative research, which collects data through observation and interviews. After conducting a program that the researcher conducted with the manager of fattening goat researchers and the manager concluded or evaluated the impact of the activities that the researcher carried out That is: 1. Getting cleaner cages. 2. Increased appetite 3. Lack of disease value in goats, 4. The air in and out of the cage is getting fresher.